Microdramaturgy of Documentary - Hadkova, Jana (Iluminace, 1992)
A review of a book by Slovak film publicist Pavol Branko on the expressive means of non-fiction film, published twenty years late for political reasons.
Keywords: non-fiction film; film theory; documentary film